A comparative study of values between College and Madrasha students of Chittagong city (Chittagong University Journal of Biological Sciences, 2013)
The aim of the present study was to investigate the difference between values of College and Madrasha Students of Chittagong city. In order to attain this purpose two groups of respondents, one consisted of 50 college students (Male = 25, Female = 25) studying in Higher Secondary level and another consisted of 50 Madrasha students (Male = 25, Female = 25) studying in Alim level were selected. An adapted Bengali version of Allport-Vernon-Lindzey study of values was used to measure theoretical, economic, aesthetic, social, political and religious values of these students. The obtained data were subjected to t test. The analysis of results indicated that the value t for theoretical (4.288), aesthetic (2.610) and religious (2.85) values were significant at .05 level but the values of t for economic (1.40), social (0.217) and political (0.49) were not significant. The findings indicated that Madrasha students posses more theoretical & religious values than college students. While, college students are more aesthetic than Madrasha students. Significant difference does not exist between Madrasha students & College students in political, economic & social values. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17086 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):87-95, 2011